Development of pictures of the contact phenomena and friction in the processes of cutting of materials - Посвятенко, Е.К.; Посвятенко, Н.І. (Problems of Tribology, 2014)
The role of friction is rotined in the processes of cutting of materials as a factor, determining a cutting temperature. It, in same queue, influences on firmness of tools, cutting speed and productivity of process. The pictures of scientists are described of friction at cutting during the last 120 years.